2017
DOI: 10.1016/j.ijfatigue.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of surface initiated rolling contact fatigue cracks in bearing steel

Abstract: Surface initiated rolling contact fatigue, leading to a surface failure known as pitting, is a life limiting failure mode in many modern machine elements, particularly rolling element bearings. Most research on rolling contact fatigue considers total life to pitting. Instead, this work studies the growth of rolling contact fatigue cracks before they develop into surface pits in an attempt to better understand crack propagation mechanisms. A triple-contact disc machine was used to perform pitting experiments on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(58 citation statements)
references
References 36 publications
3
54
0
1
Order By: Relevance
“…The model is based on stress history and damage accumulation parameters and therefore considers only crack initiation. Fatigue cracks, such as those in micropitting, also have a propagation phase, and the relative length in time of these two phases is affected by the imposed conditions [34]. In particular, crack propagation is strongly affected by the direction of sliding: negative sliding (cracked surface slower) i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The model is based on stress history and damage accumulation parameters and therefore considers only crack initiation. Fatigue cracks, such as those in micropitting, also have a propagation phase, and the relative length in time of these two phases is affected by the imposed conditions [34]. In particular, crack propagation is strongly affected by the direction of sliding: negative sliding (cracked surface slower) i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Typical patterns of crack propagation across the surface are illustrated by the SEM images, as shown in Figure C to E. It can be seen that crack growth prefers to the frictional force direction. Pawel found that visible cracks have an initial angle of inclination to the surface of 20° to 30° in bearing steel. Deng noticed that the crack propagation could be divided into two phases: First, the crack propagates obliquely downward from the bearing raceway surface with an approximate inclination angle of 30° relative to the raceway surface.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we focus on the second cracks, as seen in Figure A to C. Secondary cracks are observed to branch off the main crack and grow towards the surface, eventually liberating a fragment of the material and creating a pit formation . The secondary crack propagates into the prior austenite grain in Figures D and C but along the prior austenite grain in Figure E.…”
Section: Resultsmentioning
confidence: 99%
“…Fig.7(c) shows the enlargement of the rectangular region 2, the surface cracks were visible, the length of them is about 10-25μm. These areas continue to expand and fall off to form spalling pits and wear debirs [16]. Fig.8 shows the plastic deformation layer thickness changes with the banded carbide grade.…”
Section: Rcf Failure Observations and Mechanism Analysismentioning
confidence: 99%